Philosophical foundations of tax law - Bhandari, Monica (Oxford : Oxford University Press, 2017)
This collection brings together major themes and difficult questions in the philosophical foundations of tax law. It allows the reader to consider how tax systems should move forward in the modern world, with a sound philosophical basis, to provide the practical tax system that the state requires and citizens deserve.
This edition previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 16, 2017).
Keywords: Taxation -- Law and legislation -- Philosophy; Law; Laws of specific jurisdictions & specific areas of law